Historical mapping of canals and ditches and the Danube surface water area in the Greater Donaumoos Region over the last 235 years - Marie Kaniecki; Anne Köhler; Vera Seeburg; Natascha Mehler; Christoph Zielhofer (PANGAEA, 2025)
This dataset focuses on the historical mapping of the Greater Donaumoos fen region using old maps spanning the last 235 years. The main observations include the georeferencing of these historical maps and the subsequent vectorisation of the anthropogenic ditches and the Danube extquotesingles surface area. The data collection encompasses maps spanning multiple centuries, providing temporal coverage that highlights landscape changes over significant historical periods. The data was collected to enhance archaeological, historical, and ecological research, offering insights into past landscapes and their transformations over time. The method involved digitising old maps and applying geospatial techniques to align them accurately with current geographical coordinates (Schmidt et al., 2024). This process was essential to create vector data representing the historical state of the ditches and the Danube river in this region. The purpose of this data collection is to provide a valuable resource for researchers studying historical land use, environmental changes, and regional development. The georeferencing and vectorisation processes were conducted using QGIS, ensuring precise alignment and accurate representation of historical features. The data generated from this project is crucial for understanding how the Greater Donaumoos fen region has evolved, offering a foundational dataset for further interdisciplinary studies.